Is Encephalitozoon cuniculi of Significance in Young Dogs With Neurological Signs? - Boer, Tamar S. de; Diaz Espineira, Montse M.; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2021)
Encephalitozoon cuniculi is a microsporidium belonging to the phylum Microspora. A few reports have described the clinical significance of E. cuniculi infection in young dogs. In American and Japanese household dog populations, the seroprevalence was found to be 21%, indicating its wide-spread existence. To evaluate the clinical significance of E. cuniculi in a cohort of young dogs with neurological signs, the presence of the organism and possible response to treatment were studied. Over a 1-year period, all young dogs (<3 years old) that were referred with neurological signs were examined for the presence of E. cuniculi. Dogs were selected if serology revealed a clearly elevated IgM titer (>100) and/or if an EDTA-blood sample and/or urine sample tested positive by polymerase chain reaction (PCR). Sixteen dogs with various neurological signs were included in this study. Additional work-up included magnetic resonance imaging and cerebrospinal fluid analysis, but these revealed no abnormalities or indication of infection. All dogs were treated with fenbendazole for 10–30 days. Neurological signs disappeared completely in five dogs, 11 dogs continued to show neurological signs, and five dogs deteriorated and were euthanized, after which necropsy was performed in three. At necropsy no evidence of an E. cuniculi infection was found. We concluded that, although IgM titers and PCR indicated an E. cuniculi infection, it is most likely of limited clinical significance in young dogs.